2015
DOI: 10.1038/sdata.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Human olfactory receptor responses to odorants

Abstract: Although the human olfactory system is capable of discriminating a vast number of odors, we do not currently understand what chemical features are encoded by olfactory receptors. In large part this is due to a paucity of data in a search space covering the interactions of hundreds of receptors with billions of odorous molecules. Of the approximately 400 intact human odorant receptors, only 10% have a published ligand. Here we used a heterologous luciferase assay to screen 73 odorants against a clone library of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 41 publications
12
137
0
Order By: Relevance
“…These experiments revealed that MS4A responses occur seconds after odor presentation, with similar or slightly faster response dynamics to those observed with MOR9-1 (Figures S4D and S4E, see Experimental Procedures). Dose-response curves revealed low micromolar EC50s for three specific MS4A/odor pairs, similar to the EC50 observed for MOR9-1/vanillin (Figure 3D), and well within the range of EC50s typically observed for conventional odorant receptor/ligand pairs in vitro (Saito et al, 2009; Mainland et al, 2015). Depleting extracellular calcium abolished MS4A ligand-dependent calcium transients (Figure S4F).…”
Section: Resultssupporting
confidence: 76%
“…These experiments revealed that MS4A responses occur seconds after odor presentation, with similar or slightly faster response dynamics to those observed with MOR9-1 (Figures S4D and S4E, see Experimental Procedures). Dose-response curves revealed low micromolar EC50s for three specific MS4A/odor pairs, similar to the EC50 observed for MOR9-1/vanillin (Figure 3D), and well within the range of EC50s typically observed for conventional odorant receptor/ligand pairs in vitro (Saito et al, 2009; Mainland et al, 2015). Depleting extracellular calcium abolished MS4A ligand-dependent calcium transients (Figure S4F).…”
Section: Resultssupporting
confidence: 76%
“…The successful cloning and expression of the human olfactory receptors [32] for the development of the bioelectronic nose and the development of nano-biotechnology have improved the performance of the bioelectronic nose. The bioelectronic nose is constructed with biological materials that have been integrated with nanomaterials such as carbon nanotube, conducting polymer, and graphene [21, 27, 42, 67].…”
Section: Introductionmentioning
confidence: 99%
“…6. Sensitivities of olfactory receptors appear to be lognormally distributed for (A) flies (33) and (B) humans (34). The histograms of the logarithms of n entries of the sensitivity matrix (orange) are compared with a normal distribution (blue) with the same mean and SD λ exp .…”
Section: Discussionmentioning
confidence: 99%
“…The response of receptors to individual ligands has been measured experimentally for flies (33) and humans (34). We use these published data to estimate the statistics of realistic sensitivity matrices as described in Supporting Information.…”
Section: Optimal Receptormentioning
confidence: 99%